Smallholder dairy production systems in developing countries: Characteristics, potential and opportunities for improvement. Review - Devendra, C. (2001)
Smallholder dairy production systems in developing countries are discussed with reference to type of systems, their characteristics, potential, and opportunities for improvement. Three types of dairy systems are identified and described: smallholder systems, smallholder cooperative dairy production systems, and intensive dairy production systems. The first two systems are by far the most important, and are associated with increasing intensification. Buffaloes are especially important in South Asia, but elsewhere dairy production mainly involves Holstein Friesian cross bred cattle. Dairy goats are important in some countries, but are generally neglected in development programmes. The expansion and intensification of smallholder dairy production is fueled by increased demand for milk with associated problems of milk handling and distribution, hygiene and environmental pollution. The major constraints to production are inter alia, choice of species, breeds and availability of animals; feed resources and improved feeding systems; improved breeding, reproduction, and animal health care; management of animal manure, and organised marketing, and market outlets. These constraints provide major opportunities and challenges for research and development to increase dairy production, efficient management of natural resources, and improved livelihoods of poor farmers. Specific areas for research are identified, as also the need of a holistic focus involving interdisciplinary research and integrated natural resource management, in a shared partnership between farmers and scientists that can demonstrate increased productivity and sustainable production systems. Suggestions for performance indicators in smallholder dairy production systems are indicated.